Republic of Equatorial Guinea : 2022 Article IV Consultation-Press Release; Staff Report; And Statement By The Executive Director for Republic of Equatorial Guinea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2022)
The COVID-19 pandemic in 2020-21, and Bata explosions in 2021, struck oil-exporter Equatorial Guinea at a time when its economic vulnerabilities had already been aggravated by a prolonged period of depressed hydrocarbon prices, and seven consecutive years of decline in real GDP. The economy is slowly emerging from the ravages of the 2020-21 shocks, buoyed by higher international oil prices. However, substantial challenges remain: (i) surging food prices and banking sector vulnerabilities cloud the short term, while (ii) declining hydrocarbon production and the implied decline in external reserves loom over the medium term, especially in light of lagging governance and diversification reform implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Energy; International Agreements and Observance; International Organizations; Monetary Policy